PTU-042 Improved diagnostic yield of symptom association analysis. (June 2019) - Abdul-razakq, Humayra; Vardar, Ufuk; Raeburn, Amanda; Sweis, Rami
Abstract : Introduction: The Lyon Consensus 2018 recommends at least 3 symptoms for reliable symptom association analysis; however it is not clear if symptoms should be combined or analysed individually. This study aims to determine the impact of calculating symptom index (SI) as a measure of symptom association in combination or separately. Methods: SI measurements were collected for 139 consecutive patients who presented with reflux symptoms and received ambulatory pH monitoring at a tertiary referral centre in London. Typical symptoms were defined as heartburn (HB) and regurgitation; atypical symptoms included chest pain, belch, laryngopharyngeal reflux and others (e.g. cough). A positive SI (SI+) was considered when ≥50% of symptom events were preceded by a reflux episode within a 2 minute window. Results are presented as median (IQR; interquartile ratio). Comparisons were made using the Wilcoxon Signed Rank t-test. Results: All but one patient reported at least 3 combined symptoms. The remaining 138 patients (mean age 49 yrs; 35 males) reported a median of 30 (14, 68) symptoms overall. With all presenting symptoms combined, 13 (9.4%) patients exhibited SI+, median 73% (61%, 77%). The remaining 125 patients were SI-, median 13% (0%, 25%). When calculating symptoms individually, 25 further patients were identified with SI+ (n=38; 27.5%), thus increasing the diagnostic yield for SI+ by 3-fold; median 69% (50.5%, 99%) (p<0.001). HB in particular exhibited an additional yield of 14 patients (p=0.04). When typical symptoms were combined (HB + regurgitation), 12 further SI+ patients were identified (n=25; 18.1%), median 68% (50%, 81%) (p<0.001), thus exhibiting a 2-fold increase in the diagnostic yield. Combining atypical symptoms only resulted in 3 additional patients with SI+ (n=16; 11.6%) (p=0.067); of which belch was the predominant symptom (n=11; 68.8%). Compared to analysing all symptom together, a change in diagnosis (from SI+ to SI− or vice versa) was seen in 26 (18.8%), when symptoms were analysed separately; particularly for HB (n=12; 8.7%), combined typical symptoms (n=28; 20.3%) and combined atypical symptoms (n=20; 14.5%). Increasing the threshold for inclusion from ≥3 to ≥6 symptoms resulted in the elimination of 10 patients and led to a greater likelihood for detecting SI+ for HB (n=23; 18.0%), typical symptoms (n=23; 18.0%) and atypical symptoms (n=15, 11.7%) compared to combining all symptoms together. Conclusions: Diagnostic yield of symptom-association analysis increases (up to 3-fold) when symptoms are analysed individually than when all symptoms are combined, likely because it focuses on the most relevant symptoms that the patient complains of.